Factor Xa Acts as a PDGF-Independent Mitogen in Human Vascular Smooth Muscle Cells - Bretschneider, Ellen; Braun, Marina; Fischer, Annett; Wittpoth, Michael; Glusa, Erika; Schrör, Karsten (Thrombosis and Haemostasis, 2000)
This study investigates the mitogenic effect of the coagulation factor Xa in smooth muscle cells (SMC) from human saphenous vein and the procoagulant activity of these cells. Factor Xa elicited a concentrationdependent increase in [3H]thymidine incorporation. This mitogenic effect of factor Xa was inhibited by DX-9065a and BABCH, indicating the requirement of proteolytic activity of the enzyme. Factor Xa activated the MAP kinases ERK1/2 concentration-and time-dependently. PDGF-neutralizing antibodies neither inhibited the increase in [3H]thymidine incorporation nor ERK-1/2 phosphorylation in factor Xa-stimulated cells, suggesting that factor Xa-induced signaling and mitogenic activity in human venous SMC are independent of PDGF. Exposure of SMC to recalcified plasma resulted in a significant thrombin generation which was inhibited by anti-tissue factor antibody, tissue factor pathway inhibitor, inactivated factor VIIa and DX-9065a. These data indicate that interaction of SMC with the clotting system may contribute to venous graft disease, i.e. thrombus formation and intimal hyperplasia.
Keywords: Factor Xa; vascular smooth muscle cells; mitogenesis; thrombin generation